Effect Administration of Ethanol Extract of Bitter Melon (Momordica Charantia L.) On The Reduction of MDA (Malondialdehyde) Levels Serum in Rats Given a High-Fat Diet - Andiani, Andiani; harsa, made subhawa (Universitas Wijaya Kusuma Surabaya, 2018)
Hyperlipidemia is a disease whichthe effect in increased fat levels in the blood. In hyperlipidemia, the condition of high oxidative stress is obtained due to the oxidation process of LDL (Low Density Lipoprotein) in the body, this condition showed by increased of MDA (Malondialdehyde) levels in serum. Bitter melon (Momordica Charantia L.) contains a lot of active ingredients, one of the ingredients of bitter melon that is thought to have antilipidemic effects is flavonoid compounds. This study was experimental study using a randomized posttest only control group design study with a sample size of 30 male white rats (Rattus norvegicus) wistar strain which was divided into 3 groups, namely K1, K2, and K3. In each group, different treatments are given. Negative control group (K1), given standard feed, water ad libitum; Positive control group (K2), given standard feed, high fat feed with a dose of 2.5 ml water ad libitum; The treatment group (K3) was given a standard diet, high-fat feed with a dose of 2.5 ml water ad libitum and extract of bitter melonat a dose of 250 mg / kg BB by orally every morning for 3 weeks. Data analysis using One Way Anova Test. From the results of the test shows the significance of p-value = 0.000 which is <Î± (0.05). The results showed that there was an effect ofÂ administration ethanol extract of bitter melon (Momordica charantia L.) to decrease in serum MDA (malondialdehyde) levels in male white wistar rats (Rattus norvegicus) given a high-fat diet.